Rain rituals and hybridity in Southern Africa - Müller, R. (Verbum et ecclesia, 2008)
This article discusses the persistence and transformation of rain rituals in contemporary African Christianity. It argues that the concept ‘hybridity’ might be a useful addition to the vocabulary of scholars studying contemporary global Christianity. The use of hybridity could replace ideologically loaded terms, such as syncretism, while still describing the interaction between different religious traditions on the phenomenological level. In Africa, as elsewhere, there are ongoing internal dialogues between the often divergent traditions represented in the worldviews of contemporary Christians. Under the concept hybridity, this internal inter-religious dialogue might be well described using non-pejorative, empirical language.